Antioxidant Active Substances and Influence on Lipid Profile in White Rat Animal Experiments (Rattus norvegicus) Wistar from Kawista Fruit Extract (Limonia acidissima) - Ida Bagus Rai Wiadnya; Iswari Pauzi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Background: Kawista fruit (Limonia acidissima) from Bima Regency, West Nusa Tenggara, is empirically known for its antioxidant, tonic, and digestive properties. Its chemical components, including terpenoids, polyphenols, and flavonoids, are expected to reduce lipid profile levels. Purpose: This study aimed to identify active compounds in kawista fruit extract and evaluate its effects on lipid profile (cholesterol, triglycerides) and fasting blood glucose in white rats (Rattus norvegicus) with NAFLD-induced liver damage. Methods: An experimental approach was used. Kawista fruit extract was prepared by maceration with 70% ethanol. Rats were induced with a high-lipid diet and PTU to trigger hypothyroidism. Parameters measured included body weight, total cholesterol, triglycerides, and fasting blood glucose before and after four weeks of treatment at three dose levels. Results: Phytochemical analysis confirmed the presence of terpenoids, polyphenols, and flavonoids, but no alkaloids or saponins. Kawista extract showed a significant effect on triglyceride levels (p=0.002), while effects on cholesterol (p=0.651) and fasting blood glucose (p=0.656) were not significant. Mann-Whitney post-hoc analysis showed significant differences between all groups except between the positive control and dose 1 (p=0.885). Conclusion: Kawista fruit extract has significant potential in reducing triglyceride levels in rats with NAFLD-induced hyperlipidemia, supporting its use as a natural antioxidant and lipid-lowering agent